Apoplexy in a previously undiagnosed pituitary macroadenoma in the setting of recent COVID-19 infection. Issue 7 (28th July 2021) - Liew, Su-Yi; Seese, Rachel; Shames, Abdulrahman; Majumdar, Kalpita
Abstract : Pituitary apoplexy is an endocrine emergency, which commonly presents as hypopituitarism. Prompt diagnosis and treatment can be both life and vision saving. There are a growing number of published case reports postulating a link between COVID-19 and pituitary apoplexy. We report the case of a 75-year-old man who presented with a headache and was later diagnosed with hypopituitarism secondary to pituitary apoplexy. This occurred 1 month following a mild-to-moderate COVID-19 infection with no other risk factors commonly associated with pituitary apoplexy. This case, therefore, supplements an emerging evidence base supporting a link between COVID-19 and pituitary apoplexy.